2023
DOI: 10.2174/1573405618666220509205457
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 Vaccination Acute Disseminated Encephalomyelitis: A Case Report

Abstract: Introduction: A 67-year-old female with no significant past medical history presented to the critical care department with symptoms of encephalopathy. Case presentation: The patient’s main concerns and important clinical findings-The patient had a history of COVID -19 vaccination [recombinant ChAdOX1 nCoV-19] 14 days prior to the symptoms. The patient underwent MRI brain and cervical spine and lumbar puncture. The primary diagnoses, interventions, and outcomes- The patient was examined and was sent for MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Overall, we have identified 17 previous case reports of patients with ADEM following SARS-CoV-2 vaccination, including vaccines based on mRNA, viral vector and inactivated virus (Kania et al 2021 ; Vogrig et al 2021 ; Shimizu et al 2021 ; Lee et al 2022 ; Poli et al 2022 ; Ahmad et al 2022 ; Maramattom et al 2022 ; Rinaldi et al 2022 ; Permezel et al 2022 ; Mumoli et al 2022 ; Nagaratnam et al 2022 ; Al-Quliti et al 2022 ; Lazaro et al 2022 ; Garg et al 2022 ; Cao and Ren 2022 ; Ozgen Kenangil et al 2021 ; Yazdanpanah et al 2022 ); however, this case report is the first described case of ADEM following exposure to the Ad26.COV2.S vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we have identified 17 previous case reports of patients with ADEM following SARS-CoV-2 vaccination, including vaccines based on mRNA, viral vector and inactivated virus (Kania et al 2021 ; Vogrig et al 2021 ; Shimizu et al 2021 ; Lee et al 2022 ; Poli et al 2022 ; Ahmad et al 2022 ; Maramattom et al 2022 ; Rinaldi et al 2022 ; Permezel et al 2022 ; Mumoli et al 2022 ; Nagaratnam et al 2022 ; Al-Quliti et al 2022 ; Lazaro et al 2022 ; Garg et al 2022 ; Cao and Ren 2022 ; Ozgen Kenangil et al 2021 ; Yazdanpanah et al 2022 ); however, this case report is the first described case of ADEM following exposure to the Ad26.COV2.S vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…We have been able to identify 17 case reports that have described ADEM, including one case report of ADEM-like presentation, following a COVID-19 vaccination: seven cases with mRNA vaccine (from Moderna and Pfizer), (Kania et al 2021 ; Vogrig et al 2021 ; Shimizu et al 2021 ; Lee et al 2022 ; Poli et al 2022 ; Ahmad et al 2022 ; Maramattom et al 2022 ) seven cases with a viral vector vaccine (from AstraZenica and Sputnik V) (Rinaldi et al 2022 ; Permezel et al 2022 ; Mumoli et al 2022 ; Nagaratnam et al 2022 ; Al-Quliti et al 2022 ; Lazaro et al 2022 ; Garg et al 2022 ) and three cases with vaccines based on inactivated virus (from SinoVac and Sinopharm) (Cao and Ren 2022 ; Ozgen Kenangil et al 2021 ; Yazdanpanah et al 2022 ). However, this case report is the first described case of ADEM following exposure to the Ad26.COV2.S vaccine from Johnson & Johnson.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has been identified (8) including 20 studies, out of which 19 were eligible to be included in our review: (9,10,(19)(20)(21)(22)(23)(24)(25)(26)(27)(11)(12)(13)(14)(15)(16)(17)(18) (Figure 1) In addition to the 19 studies included, our literature search has identified nine other studies: (28)(29)(30)(31)(32)(33)(34)(35). Thus, a total of 28 studies were analysed comprising a total of 38 cases.…”
Section: Resultsmentioning
confidence: 99%
“…However, in 9442 AEFI reported in the Vaccine Adverse Event Reporting System (VAERS) of the Centers for Disease Control (CDC) 2.69% of cases presented with severe neurological manifestations 1 . A recent systematic review 2 analyzing the spectrum of such severe neurological complications differentiated between cerebral involvement, especially cerebrovascular events and inflammatory diseases 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 , spinal cord damage such as transverse myelitis 1 2 4 23 24 cranial and peripheral nerve involvement 2 4 25 and muscle affections, e. g. myositis 2 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Neurological key symptoms are headache, neuropsychological deficits, disorientation and dizziness 33 . ADEM associated with COVID-19 vaccination is rare and review of the literature currently yielded 22 cases with documented additional MR imaging abnormalities 2 3 4 5 6 7 8 9 10 11 13 14 16 18 19 20 21 22 . We report on another two cases of acute encephalitis and ADEM following COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%